The Role of Notaries in Supporting Efforts To Settle Problem Credit at People's Credit Banks - Partini, Partini; Shallman, Shallman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Banks in running their business to provide loan/credit services to the public really need Notaries and PPAT to assist in making notarial deeds of agreements and binding collateral. In making credit agreements, of course, the Bank and the borrowing customer (debtor) must pay attention to the contents of the credit agreement they signed, starting from the definition, obligations arising from the agreement, and the consequences of default that provide certainty to the bank to be able to make settlement efforts and provide legal protection in accordance with the provisions of applicable laws and regulations. This study aims to determine the role of notaries in providing support to banks in efforts to resolve their problem loans and also to determine the obstacles notaries face in providing support to banks for the resolution of problem loans. The problems in this study are analyzed using the theory of legal certainty and the theory of legal protection. The research approach uses a sociological juridical approach, which is qualitative in nature with the research specification being descriptive analysis and data analysis using qualitative descriptive methods. The primary data collection method was obtained through guided interviews with related parties, supported by secondary data obtained from the literature as supplementary reference material. The results of this study The role of Notaries in supporting efforts to resolve problematic loans in banks include ensuring the perfection of the deed made by the notary must be in accordance with the provisions in order to have binding legal force, Conducting ratification of the addendum to the credit agreement on efforts to resolve problematic loans through credit restructuring in accordance with the provisions, Providing clear legal education to debtors in order to better understand their obligations and rights as well as the legal consequences of the impact of default that occurs and can assist the Bank in the AYDA (Collateral Taken Over) process by making a PPJB (Sale and Purchase Binding Agreement) so that sales can be carried out in the future. The obstacles are the busy schedule of the notary himself to carry out the addendum agreement, and the existence of an APHT process that has not been completed but the credit is about to mature and is problematic due to the provisions of the stages at the land office. And the suggestion is that Notaries must be professional in accordance with the Notary Law by upholding the code of ethics. Notaries in carrying out collateral binding must pay attention to the Laws that regulate guarantees in accordance with the Fiduciary Guarantee Law and the Law on Mortgage Rights. Notaries can provide legal education to problem debtors at partner banks when making addendum agreements for credit restructuring or other matters. Keywords: Banks; Credit; Efforts to Resolve Problematic Credit; The Role of Notaries.